“Diagnosis of the asymmetry autonomous work in the learning English language with the students of Décimo Grado de Educación General Básica “a” at Unidad Educativa “Fernando Daquilema” city of Riobamba, Chimborazo province, during the academic term February – July 2016” - Caba Aucancela, Janneth Rocio (2016)
This research was done with the students of Tenth Grade of Basic General Education, Room “A” at “Fernando Daquilema” high school, Riobamba city. This research was to diagnose the autonomous work asymmetry in the English language learning, to know if some students are autonomous and others are not. The population of this research was 32 students. The research work was qualitative through the ethnographic method, which helps to describe and analyze ideas, belief, meaning, knowledge and practices in the students’ field. For data collection a survey was applied and the instrument was a questionnaire, which the data were collected for the analysis and interpretation for the corresponding results. Consequently, the theoretical framework was developed to provide scientific and educational information that allows to contrasting the different point of views of the authors. Finally, it was determined that the autonomous work asymmetry has differences in the academic area.